Uwagi o odpowiedzialności dyscyplinarnej sędziów za rażącą i oczywistą obrazę prawa w polskim systemie prawnym - Mazur, Paweł (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2017)
The paper deals with the disciplinary responsibility of judges for obvious and flagrant legal misconduct. A model of the aforementioned responsibility in the Polish law has been presented. The problems deliberated upon include: the moral justification of punishing judges for mentioned disciplinary delicts and critical evaluation of Supreme Court view about this responsibility. A question is asked about reconsidering the interpretation of obvious and flagrant legal misconduct according to modern times and the complicated social and law reality.
Notes on Disciplinary Responsibility of Judges for Blatant and Obvious Violations of Law in Polish Legal System
Keywords: disciplinary responsibility; judges; misconduct; Supreme Court; Polish legal framework